Decreasing motor stereotypy in leisure contexts: Analysis of stimulus control with response interruption and redirection. (4th December 2019) - Falligant, John M.; Dommestrup, Aila K.
Abstract: Noncontingent access to preferred stimuli and activities may decrease stereotypic behavior in individuals with autism or other developmental disorders. However, prompted engagement, response interruption and redirection (RIRD), and/or contingent access to stereotypy may be required to achieve clinically significant reductions in stereotypy. Antecedent stimuli may also be manipulated during intervention to establish stimulus control by signaling when stereotypy will receive programmed consequences. The purpose of the current project was to replicate prior research in this area by a) evaluating the effectiveness of RIRD on motor stereotypy in an adolescent with autism and b) providing contingent access to stereotypy as a function of successively longer intervals without stereotypic behavior. We also assessed the extent that these procedures gained acceptable stimulus control. Results from this project suggest RIRD and contingent access to stereotypy may effectively decrease motor stereotypy in leisure contexts, though consistent inhibitory stimulus control may be difficult to establish.